Cellulose biomembrane versus collagenase dressing for the treatment of chronic venous ulcers: a randomized, controlled clinical trial - Colenci, Raquel [UNESP]; Miot, Hélio A. [UNESP]; Marques, Mariângela E. A. [UNESP]; Schmitt, Juliano V. [UNESP]; Basmaji, Pierre; Jacinto, Jéssica dos Santos [UNESP]; Abbade, Luciana P. F. [UNESP] (JLE, 2019)
Background: Cellulose biomembranes may be used for difficult-to-treat ulcers. Objectives: To assess the efficacy and safety of cellulose biomem-branes compared to a collagenase dressing for the treatment of chronic venous ulcers. Materials and Methods: A randomized, controlled clinical trial was performed using two groups: one treated with collagenase dressing and the other with cellulose biomembrane over a 90-day (T90) period. Both groups received compression therapy. The primary outcome was reduction in ulcer area at T90. Secondary outcomes were healing status, decrease in devitalized tissue and exudate, vascular fraction, change in quality of life, and safety. Results: We randomized 46 participants with 73 venous ulcers (21 with 36 ulcers in the collagenase group and 25 with 37 ulcers in the biomembrane group). A decrease in ulcer area occurred at T90 in both groups, but the difference was not significant. Complete healing before T90 occurred for seven ulcers in the collagenase group and 12 ulcers in the biomembrane group, without significant difference. However, the biomembrane promoted increased precocious healing (p = 0.02). Improved bed vitality and quality of life was observed as a function of time (p <. 0.01), but this was not significant between the groups. Immunohistochemical analysis of CD34 showed an increase in vascular fraction in both groups (p< 0.01), with a higher level in the biomembrane group (p < 0.05). No adverse events were considered related to the products. Conclusion: Cellulose biomem-branes, in combination with compressive therapy, are effective and safe for the treatment of venous ulcers and provide results similar to those with collagenase treatment.
Keywords: cellulose biomembrane; chronic venous ulcer; clinical trial; collagenase; therapy